Second language writing systems - Cook, Vivian, 1940-2021; Bassetti, Benedetta (Second language acquisition (Clevedon, England) ;, 2005)
This is the first book to treat the acquisition and use of a second language writing system. Drawing from a variety of disciplines and writing systems, it investigates how people read, write and analyse a writing system that represents a second language.